1987
DOI: 10.1002/tera.1420360110
|View full text |Cite
|
Sign up to set email alerts
|

Developmental effects of isotretinoin and 4‐oxo‐isotretinoin: The role of metabolism in teratogenicity

Abstract: Previous observations have indicated that isotretinoin (IT), a drug in common use for therapy of cystic acne, is teratogenic in humans but possesses low embryotoxicity in pregnant mice, probably because of its shorter half-life and limited placental transfer in rodents. In human volunteers and patients, one major blood metabolite of IT is 4-oxo-isotretinoin (4-oxo-IT) which undergoes slower elimination than IT and may itself be a participant in teratogenesis. To investigate the problem of species differences d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…At present it is unknown to what extent the oxidized, teratogenic metabolites contribute to the embryotoxicity of all-J..[llm-RA and 13-lli-retinoic acid (13-lli-RA, isotretinoin). These observations are consistent with those of Goulding and Pratt (1986), Webster et al (1986), and Kochhar and Penner (1987), who found the 4-oxo metabolite of 13-ill-RA equipotent to 13-ill-RA in intact pregnant ICR or C57 Bl/6J mice, cultured CO-l mouse embryos, cultured CFHB rat embryos, and cultured ICR mouse forelimb buds. 4-0xoretinoic acid was nearly as active as all-trans-RA in the hamster tracheal organ culture assay (4-oxoretinoic acid ED50 = 700 pM; all-J..[llm-RA ED50 = 30 pM) (Newton et al, 1980).…”
Section: Discussionsupporting
confidence: 91%
“…At present it is unknown to what extent the oxidized, teratogenic metabolites contribute to the embryotoxicity of all-J..[llm-RA and 13-lli-retinoic acid (13-lli-RA, isotretinoin). These observations are consistent with those of Goulding and Pratt (1986), Webster et al (1986), and Kochhar and Penner (1987), who found the 4-oxo metabolite of 13-ill-RA equipotent to 13-ill-RA in intact pregnant ICR or C57 Bl/6J mice, cultured CO-l mouse embryos, cultured CFHB rat embryos, and cultured ICR mouse forelimb buds. 4-0xoretinoic acid was nearly as active as all-trans-RA in the hamster tracheal organ culture assay (4-oxoretinoic acid ED50 = 700 pM; all-J..[llm-RA ED50 = 30 pM) (Newton et al, 1980).…”
Section: Discussionsupporting
confidence: 91%
“…Cartilage-specific proteoglycan is a marker of the differentiated phenotype of chondrocytes (Benya and Padilla, 1986). Retinoids are also known to inhibit chondrogenesis in cell culture systems (Kochar and Penner, 1987;Eckhardt and Schmitt, 1994). Thus, a direct effect of retinoids on the differentiation state of chondrocytes could be an important mechanistic component of retinoid-induced epiphyseal plate closure.…”
Section: Discussionmentioning
confidence: 99%
“…?_), has been utilized for the treatment of dermatologic disorders since 1982 (8). Retinoic acids have been reported to produce multiple abnormalities including limb deformities, heart de fects, and facial malformations in mammals and have similar teratogenic effects in humans (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%